2007
DOI: 10.1002/cbic.200700383
|View full text |Cite
|
Sign up to set email alerts
|

Macrocyclic Statine‐Based Inhibitors of BACE‐1

Abstract: Minimal sequence requirements for binding of substrate-derived statine peptides to the aspartyl enzyme were established on the basis of the X-ray cocrystal structure of the hydroxyethylene-octapeptide OM00-3 in complexation with BACE-1. With this information to hand, macrocyclic compounds that conformationally restrict and preorganize the peptide backbone for an entropically favoured binding to the enzyme active site cleft were designed. By means of a side chain-to-side chain ring closure between two aspartyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…[21][22][23][24] In an interesting study, solution structures of statine-based cyclic peptidic inhibitors were determined by NMR spectroscopy, energetics of binding to its target, the aspartyl protease BACE-1 (β-secretase) was measured by ITC and the structure of the complex was determined by X-ray crystallography. 25 These statinebased cyclic peptidic inhibitors were optimized to adopt a preorganized conformation in solution that reduced the entropic loss upon formation of complex with BACE-1. Similarly, the rather large entropic contribution of upain-1 binding to uPA opens up the possibility of improving the affinity of the core peptide by reducing the entropic loss during binding without affecting the binding mode (ΔH) of the peptide.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24] In an interesting study, solution structures of statine-based cyclic peptidic inhibitors were determined by NMR spectroscopy, energetics of binding to its target, the aspartyl protease BACE-1 (β-secretase) was measured by ITC and the structure of the complex was determined by X-ray crystallography. 25 These statinebased cyclic peptidic inhibitors were optimized to adopt a preorganized conformation in solution that reduced the entropic loss upon formation of complex with BACE-1. Similarly, the rather large entropic contribution of upain-1 binding to uPA opens up the possibility of improving the affinity of the core peptide by reducing the entropic loss during binding without affecting the binding mode (ΔH) of the peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported macroheterocyclic peptidomimetic inhibitors of β-secretases (Fig. 8c, d) that fit into the relatively large-size active site of the aspartic peptidase [109,[121][122][123][124]. Macrocyclic ethers and lactones have been used to pre-organize and stabilize bioactive conformations with improved activity and physicochemical properties relative to the linear counterparts (reviewed in [125]).…”
Section: Protease Inhibitorsmentioning
confidence: 99%
“…[Barrow et al, 2008]; and (9) tyramines [Kuglstatter et al, 2008]. Some of the designs also introduce macrocyclic constraints [Barazza et al, 2007;Hanessian et al, 2006;Lindsley et al, 2007;Rojo et al, 2006;Stachel et al, 2006] based on the observation of close contacts between portions of the inhibitors as bound in the BACE-1 active site.…”
Section: Structure-based Designmentioning
confidence: 99%